Pemuda (Pe)kerja Paruh Waktu: Dependensi dan Negosiasi - Nanda Harda Pratama Meiji (Universitas Gadjah Mada, 2019)
Part-time work is a relatively common thing for young people today. Unlike the previous decade, now, part-time jobs offered are mushrooming with various types of activities. Similarly, Indonesia offers a variety of part-time jobs to its main students. Malang, a city of education with thousands of students in it, also competing to take part in working part-time. This study seeks to focus on the aspects of dependency and negotiation carried out by students who take part-time jobs, especially at coffee shops. This phenomenon is because the culture of